Instalasi Air Bersih Sistem Tertutup di Mushola Al-Muqoramah Desa Serdang Kulon Kabupaten Tangerang - Yenni Arnas; Benny Kurnianto; Hari Kurniawanto; KGS M Ismail; Imam Haryadi Wibowo (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
Based on the observations of the Al-Muqoramah prayer room (mushola) in Serdang Kulon Village Tangerang Regency, there are several facilities that has not met standards. There was no standardized-installation of clean water supply and proper toilet facilities. In this community service activities, several things are carried out that is expected to be a solution to the problem of those facilities. First, the clean water supply system would be improved by replacing water pumps, providing water reservoirs, installing automatic pump systems including piping and providing ablution places (wudhu) to ensure the availability of clean water. Then, a proper restroom facilities was build. It is expected that in the future the clean water facilities that have been built by the Community Partnership Service (PKM) team can be a standard for the construction of facilities of prayer room, especially in the rural areas.